2017
DOI: 10.1007/s00266-017-0858-3
|View full text |Cite
|
Sign up to set email alerts
|

Use of Computer Imaging in Rhinoplasty: A Survey of the Practices of Facial Plastic Surgeons

Abstract: This journal requires that authors assign a level of evidence to each article. For a full description of these Evidence-Based Medicine ratings, please refer to the Table of Contents or the online Instructions to Authors www.springer.com/00266 .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…Despite the fact that computer imaging has been a concrete vehicle of communication during the rhinoplasty consult for the last 30 years now, 7 its use has long been a topic of debate among facial plastic surgeons. 29 Our work is expected to move us toward achieving better patient selection and therefore satisfaction in the future, as long as morphing is endorsed in a much larger scale by rhinoplasty surgeons across the globe.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the fact that computer imaging has been a concrete vehicle of communication during the rhinoplasty consult for the last 30 years now, 7 its use has long been a topic of debate among facial plastic surgeons. 29 Our work is expected to move us toward achieving better patient selection and therefore satisfaction in the future, as long as morphing is endorsed in a much larger scale by rhinoplasty surgeons across the globe.…”
Section: Discussionmentioning
confidence: 99%
“…In a large survey of 1,200 facial plastic surgeons in the United States, it was found that 63% of them were using computer imaging for their rhinoplasty consultations. 29 However, morphing is less common in practice in other parts of the globe. Despite the fact that computer imaging has been a concrete vehicle of communication during the rhinoplasty consult for the last 30 years now, 7 its use has long been a topic of debate among facial plastic surgeons.…”
Section: Discussionmentioning
confidence: 99%
“…17 Computer imaging is becoming an increasingly popular tool for preoperative evaluation and surgical planning in rhinoplasty, serving a similar function to the rhinoplasty worksheet. 18 With the advent of 3D imaging, this technology has advanced to be able to provide precise facial measurements preoperatively and simulate postoperative results. 19 These images can facilitate communication and set expectations for patients, possibly increasing their postoperative satisfaction.…”
Section: Surgical Planningmentioning
confidence: 99%
“…These are beyond the scope of this study but include more detailed and specific preoperative assessment and improved photography with three-dimensional imaging and modeling. [170][171][172][173] The recognition of the changing psychology of rhinoplasty patients, and the importance of properly selecting patients, is being emphasized to achieve an improved quality of life outcome in contradistinction to merely a surgical result. Perioperative care has improved dramatically, with diminished anesthetic risks, pain, dressings, and recovery time being the norm.…”
Section: Nonsurgical Advances In Perioperative Management Of Rhinoplamentioning
confidence: 99%